FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN (Studi Empiris pada seluruh Perusahaan yang terdaftar di Bursa Efek Indonesia Tahun 2010) - Hary Ardian; Surya Rahardja (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the factors that influence of Corporate Social Responsibility (CSR) and Environment Disclosure at the corporate’s annual reports in Indonesia. The factors that influence of Corporate Social Responsibility (CSR) and Environment Disclosure is leverage, profitability, board of directors, firm’s size, BUMN Company and Non BUMN Company.The population in this study is all of Indonesian firms in Indonesian Stock Exchange (IDX) 2010. Total sample in this research are 84 firms that selected with purposive sampling. This study uses content analysis of CSR disclosure by using Reporting Guidelines contained in the General Reporting Initiatives (GRI). The data analysis technique with classical assumption test. Testing of hypotheses using multiple linear regression analysis with spss 17.0 for windows.Result of this study indicates board of director’s, firm’s size, BUMN company had a significant effect to CSR disclosure in Indonesia. In the other hand, leverage ratio and profitability didn’t success to give positive influence for Corporate Social Responsibility Disclosure in Indonesia